Determinants of preterm birth: Pelotas, Rio Grande do Sul State, Brazil, 2004 birth cohort Determinantes de nascimento pré-termo na coorte de nascimentos de 2004, Pelotas, Rio Grande do Sul, Brasil - Mariângela F. Silveira; Cesar G. Victora; Aluísio J. D. Barros; Iná S. Santos; Alicia Matijasevich; Fernando C. Barros (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
Prematurity is a leading cause of neonatal mortality and a global health problem that affects high, middle and low-income countries. Several factors may increase the risk of preterm birth. In this article, we test the hypothesis that different risk factors determine preterm birth in different income groups by investigating whether risk factors for preterm deliveries in the 2004 Pelotas (Rio Grande do Sul State, Brazil) birth cohort vary among those groups. A total of 4,142 women were included in the analysis. Preterm births were equally common among women who had spontaneous vaginal deliveries as for those with induced or operative births. In the multivariate analysis the factors that remained significantly associated with preterm birth were black skin color, low education, poverty, young maternal age, primiparity, previous preterm birth, inadequacy of prenatal care and reported hypertension. In the analyses repeated after stratification by family income terciles, there was no evidence of effect modification by income and no clear difference between the socioeconomic groups. No association between cesarean section and preterm delivery was found. Further studies are required to understand the causes of the epidemic of preterm births in Brazil. A prematuridade é uma grande causa de morte neonatal e um problema de saúde global, afetando países de alta, média e baixa renda. Vários fatores podem aumentar o risco de parto pré-termo. Neste artigo, testamos a hipótese de que diferentes fatores de risco determinem o parto pré-termo em diferentes grupos de renda, investigando como fatores de risco para prematuridade na coorte de nascimentos de 2004 de Pelotas, Rio Grande do Sul, Brasil, variam entre estes grupos. Foram incluídas na análise 4.142 mulheres. Os nascimentos pretermo foram igualmente comuns entre mulheres com partos vaginais e com partos induzidos ou cesáreas. Na análise multivariada, a cor negra, baixa educação, baixa renda, idade materna jovem, primiparidade, parto pré-termo anterior, cuidado pré-natal inadequado, e relato de hipertensão na gestação permaneceram significativamente associados com prematuridade. Nas análises estratificadas por tercis de renda familiar não houve evidência de modificação de efeito por renda, não sendo identificados diferentes padrões de risco entre os grupos sócio-econômicos. Não foi encontrada associação entre o parto cesáreo e prematuridade. Mais estudos são necessários para entender as causas da epidemia de partos pré-termo no Brazil.